Tourism and Tradition: Heritage Conservation Practices and Challenges Amid Mass Tourism in Kathmandu Valley - Karki, Dipendra; Dahal, Rewan Kumar; Ghimire, Binod; Joshi, Surendra Prasad (Journal of Innovation in Academia, 2024)
The increasing popularity of prominent tourist destinations has raised significant concerns about the adverse impacts of mass tourism on cultural heritage sites and their surrounding environments. This study explores the cultural heritage conservation practices and challenges in Kathmandu employing a cross-sectional descriptive and explanatory design. Data was collected through surveys using structured questionnaires and interviews. Systematic random sampling was employed to select local community members, while purposive sampling was used for interviews with government officials, cultural experts, and tourism authorities. The study’s sample size is 395 with valid responses from respondents. Latent class analysis indicated three main visitor types: heritage enthusiasts, spiritual seekers, and urban explorers. Thematic analysis of seven interviews with key stakeholders revealed seven major impediments to effective heritage conservation: inadequate management, insufficient monitoring and evaluation, lack of financial resources, minimal stakeholder involvement, the pressures of urbanization, weak governmental commitment, and the impacts of vandalism and illicit trafficking. The findings from the multi-method analysis suggest that the cultural heritage sites in Kathmandu Valley are at risk unless supported by robust conservation strategies, including comprehensive site management plans, research-driven policies, and increased stakeholder and community participation. The study emphasizes the need to integrate heritage conservation with sustainable development initiatives, advocating for enhanced promotion of conservation practices as a means to achieve both economic and social sustainability. The research offers evidence-based policy recommendations aimed at mitigating the effects of mass tourism and safeguarding the cultural and historical integrity of Kathmandu’s heritage sites.